THE SUITABILITY OF TWO- YEAR- OLD POPLAR CLONES FOR PRODUCTION OF PARTICLEBOARD - Abdolrahman Hosseinzadeh (Regional Information Center for Science and Technology (RICeST), 2004)
Decreasing availability of raw material for Iranian wood industries and the need to conserve our limited natural forests initiated research concerning the utilization of fast-growing species in particleboard production. The objective of this study was to investigate the possibility of particleboard production from wood of two- year- old coppices of 17 experimental populus clones grown under intensive culture in the "Alborz Research Center" near Tehran. The furnish contained mixture of stem and branch wood with bark used to make 51 sample boards (3 board from each clone). Modulus of elasticity (MOE), modulus of rupture (MOR), internal bond strength (IB), thickness swelling and water absorption of the specimens were tested. The results indicate that sample boards made from Populus euramericana costanzo and populus euramericana 561.41 had significantly the highest MOR and MOE. But there was no significant differences in the internal bonding strength between different clones, while, those sample boards made from populus nigra betulifolia and Populus nigra nivea showed significantly the lowest percentages of thickness swelling. The average physical and mechanical properties of the particleboard samples produced from two- year- old coppices of poplar clones compared favourably to boards made from natural grown beech wood. Therefore, using UF resin, particleboard with acceptable quality particleboards can be produced from two- year- old poplar clones.